Exploring the inhibitory effect and mechanism of isorhamnetin therapy on oral squamous cell carcinoma based on network pharmacology and molecular docking - YU Fangfang, ZHOU Jingjing, YANG Jie, QU Huijuan, HUI Guangyan (口腔疾病防治)
Objective To explore the mechanism of isorhamnetin (Iso) in the treatment of oral squamous cell carcinoma (OSCC) using network pharmacology and molecular docking methods and to verify it in vitro. Methods The key targets were obtained by constructing the PPI protein interaction network based on the common intersection targets of Iso-OSCC. At the same time, gene ontology (GO) and Kyoto encyclopedia of genes and genomes (KEGG) were used to analyze the related signaling pathways of the intersection targets. Iso and core targets were also analyzed through molecular docking and visualization. Colony formation assay and Transwell assay were used to identify the effect of Iso on the proliferation and invasion of Cal-27 cells. Western blot was used to analyze the regulatory effects of different concentrations of Iso on estrogen receptor-1 (ESR1), phosphoinositide-3-kinase regulatory subunit-1 (PIK3R1), Src tyrosine kinase (SRC), and phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT) signaling pathway proteins. Results A total of 269 potential intersection targets of Iso-regulated OSCC were obtained. According to the degree obtained by topological analysis, PIK3R1, AKT1, SRC, ESR1, and other core targets were screened out. KEGG analysis showed that 165 signaling pathways were enriched in the intersection targets of Iso-OSCC, among which the PI3K/AKT signaling pathway played an important role in the treatment of OSCC with Iso. Molecular docking results showed that the absolute value of binding energy between target proteins PIK3R1, AKT1, SRC, ESR1, and Iso was high. After Cal-27 cells were treated with Iso, the number of cell colony formations, the number of transmembrane cells, and the expression of PIK3R1, ESR1, SRC, p-PI3K, and p-AKT were negatively correlated with the increase in Iso concentration (P < 0.05). Conclusion Iso can inhibit PI3K/AKT signal transduction and influence the expression of PIK3R1, AKT1, SRC, and ESR1 proteins, thereby inhibiting the occurrence and development of OSCC.